PENGARUH KOMBINASI NUTRISI TERHADAP PERTUMBUHAN DAN HASIL TANAMAN SELADA MERAH (Lactuca sativa var. Lollorosa) PADA HIDROPONIK SISTEM WICK - Ridwan Kusuma Wardhana; Darso Sugiono; Yayu Sri Rahayu (Jurusan Budidaya Tanaman Perkebunan, Politeknik Pertanian Negeri Pangkajene Kepulauan, 2023)
Lettuce is a plant whose leaves are taken to be used as vegetables or salad. The purpose of this study was to obtain a combination of nutrients that can increase the growth and best yield of red lettuce (Lactuca sativa var. Lollorosa) with hydroponic wick system. The research method used in this study was a single-factor Randomized Group Design (RAK) consisting of 7 treatments repeated 4 times. The treatments applied were A (AB Mix 3.2 EC), B (AB Mix 1.5 EC + Bayfolan 6 ml), C (AB Mix 1.8 EC + Bayfolan 3 ml), D (AB Mix 1.2 EC + Bayfolan 9 ml), E (AB Mix 1.5 EC + POC 6 ml), F (AB Mix 1.8 EC + POC 3 ml), and G (AB Mix 1.2 EC + POC 9 ml). Giving a combination of nutrients gives a real effect on the growth and yield of red lettuce plants (Lactuca sativa var. Lollorosa) at the age of 2 weeks after planting, 3 weeks after planting, 4 weeks after planting, 5 weeks after planting. Number of leaves at plant age 3 weeks and 5 weeks. Leaf area, root length, fresh weight of plants with roots, fresh weight of plants without roots. Treatment E, namely AB Mix 1.5 EC + POC 6 ml, gave the highest results on plant height, which was 20.96 cm, root length of 26.94 cm, leaf area of 100 cm2, fresh weight with roots of 13.3 g, and fresh weight without roots of 11.49 g